Effect of planting geometry, direction of planting and sulphur application on growth and productivity of sesame (Sesamum indicum) - SARKAR, R K; BANIK, P (The Indian Journal of Agricultural Sciences, 2014)
A field experiment Was conducted during the spring season of 1999 and 2000 to study the effect of planting geometry, direction of planting and sulphur application on growth and productivity of sesame (Sesamum indicum L.) in gangeticalluvial (Entisol) land. Planting geometry of 45 cm x 15 cm enhanced certain physiological growth parameters like leaf-area index and nat assimilatior, rate over other geametries of 30 cm x 30 cm and 45 cm x 30 cm. Despite reduction in yield attributes with erop geometry of 45 cm x 15 cm, there wits higher seed yield under this treatment mainly owing to optimum plant population per unit area. Planting in north-south direction, and an application 0[50 kg Siha improved sesame growth in terms of leaf-area index, crop-growth rate, relative growth rate, net assimilation rate and various yield attributes which eventually led to higher yield of the crop over east-west direction of planting and 25 kg S/ha. Despite reduction in net assimilation rate with 50 kg S/ha, yield was not at all impaired probably because of a good balance between photosynthesis and respiration.